Pengaruh Lengas Nisbi dan Suhu terhadap Kerusakan Gaplek Akibat Aspergillus flavus Selama Penyimpanan - H. A. Oramahi; Christanti Sumardiyono; Nursamsi Pusposendjojo; Haryadi Haryadi (Universitas Atma Jaya Yogyakarta, 2010)
A study on the spoilage of dried cassava by Aspergillus flavus was still limited so that such study is very important to do. This experiment was done to examine the effect of relative humidity (RH) and storage room temperature on the development of A. flavus and dried cassava spoilage during storage time. Based on the population of A. flavus, starch content, reduction sugar content, and water content of dried cassava, it was concluded that RH 65%, the temperature of 30 and 35oC had better storage condition for dried cassava because it resulted in the lowest population of A. flavus and the lowest deterioration of dried cassava.